Investigating the motivation, participation, and achievement of students: a comparative study of gender-based EFL classroom - Muhaiminah Akib; Haryanto; Iskandar; Andi Anto Patak (International Journal of Humanities and Innovation (IJHI), 2018)
This research focused on students’ motivation, class participation and achievement in male and female class as well as mixed class. The research used the quantitative method to investigate the students’ motivation, participation, and achievement in different classroom compositions. The findings of this research indicated that there is no difference in students’ motivation in gender-based EFL classroom. Male class gained the highest scores in performance goal and achievement goal in factors of motivation. Meanwhile, female class gained the highest scores in science learning value, and learning environment stimulation and mixed class gained the highest scores in self-efficacy and active learning strategy. Students’ participation in gender-based EFL classroom for male class gained the highest scores in all factors of participation. It means that students of male class more participate in EFL class than students of female class and mixed class.